PsycEXTRA Dataset 2009
DOI: 10.1037/e546742012-001
|View full text |Cite
|
Sign up to set email alerts
|

The mathematics and science teacher shortage: Fact and myth

Abstract: Contemporary educational thought holds that one of the pivotal causes of inadequate school performance is the inability of schools to adequately staff classrooms with qualified teachers, especially in fields such as mathematics and science. Shortages of teachers, it is commonly believed, are at the root of these staffing problems, and these shortfalls are, in turn, primarily due to recent increases in teacher retirements and student enrollments.The objective of this study is to empirically reexamine the issue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…Despite the importance of teacher quality to student success, school districts across the United States struggle with obtaining high‐quality teachers for schools serving low‐income students (Jacob, ; Monk, ). These challenges are more serious in particular academic subjects, especially math and science at the secondary level (Ingersoll & May ; Ingersoll & Perda, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of teacher quality to student success, school districts across the United States struggle with obtaining high‐quality teachers for schools serving low‐income students (Jacob, ; Monk, ). These challenges are more serious in particular academic subjects, especially math and science at the secondary level (Ingersoll & May ; Ingersoll & Perda, ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, Goldrick, Osta, Barlin, and Burn (2013) reported that there is an increasing influx of beginning teachers in today's classrooms. Particularly, a shortage of teachers in the field of science and mathematics is evident when considering the supply of new teachers-when balanced against the losses of teachers-due to retirement, preretirement teacher turnover, and other factors (Ingersoll & Perda, 2009). Particularly, a shortage of teachers in the field of science and mathematics is evident when considering the supply of new teachers-when balanced against the losses of teachers-due to retirement, preretirement teacher turnover, and other factors (Ingersoll & Perda, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, schools are confronted with the phenomenon of a "revolving door" (Smith & Ingersoll, 2004, p. 706) in terms of their staffing situations. Rather, the elements of a school's overall environment, its differences, characteristics, and other conditions are considered as major factors-as they pertain to retention-especially for beginning teachers (Ingersoll & Perda, 2009;. recent report indicated that the teaching community is getting greener while becoming less stable.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, in larger districts there are more resources available through the district and curriculum specialists devoted to supporting science teachers, especially when they are teaching outside of their main endorsements. In small rural schools, where there may only be one science teacher at a single high school, science teachers are especially challenged to teach all areas of science equally well (Ingersoll and Perda, 2009). On the whole, in our study we found that the science teachers we interviewed noted that it takes time, effort, and money to seek out professional development in ESS because it is not offered by their school districts and many Nebraska school districts are too small to have a science-specific curriculum coordinator to assist them.…”
Section: Challenges To High School Ess Educationmentioning
confidence: 99%